Economic evaluation of production capacity for natural gas hydrate industrial exploitation in the South China Sea - Wu, Linqiang; Zhang, Tao; Zhang, Hongtao; Sui, Yuzhang; Yu, Xinghe; Miao, Miao (Frontiers in Earth Science, 2022)
Natural gas hydrate (NGH) is a worldwide strategic and prospecting commercial resource in the 21st century. The industrialization of NGH has great strategic significance for the achievement of peak carbon dioxide emissions and carbon neutrality. Prior to its industrialization, an economic evaluation of production capacity for each well per day should be conducted to determine whether it is profitable at different given gas prices. In this study, a new hybrid method based on the discounted cash flow (DCF) method and the energy return on investment (EROI) method is used to estimate the economic production rate of NGH exploitation at four different gas price scenarios. The results show that the lowest production rate to make NGH exploitation economic ranges from 1.96 to 29.60 × 104 m3/d/well. With the change in the number of wells, gas–water ratio, gas price, decreasing rate in production cost, and sensitivity analysis are carried out. It shows that all these key factors have a significantly negative effect on the economic production rate initially, and then the sensitivity to the economic production rate will become lower and lower with the rising value of each key factor.